Genetic Differentiation of North-East Argentina Populations Based on 30 Binary X Chromosome Markers - Di Santo Meztler, Gabriela P.; del Palacio, Santiago; Esteban, María E.; Armoa, Isaías; Argüelles, Carina F.; Catanesi, Cecilia I. (Frontiers in Genetics, 2018)
Alu insertions, INDELs and SNPs in the X chromosome can be useful not only for revealing relationships among populations but also for identification purposes. We present data of 10 Alu insertions, 5 INDELs and 15 SNPs of X-chromosome from three Argentinian north-east cities in order to gain insight into the genetic diversity of the X chromosome within this region of the country. Data from 198 unrelated individuals belonging to Posadas, Corrientes, and Eldorado cities were genotyped for Ya5DP62, Yb8DP49, Ya5DP3, Ya5NBC37, Ya5DP77, Ya5NBC491, Ya5DP4, Ya5DP13, Yb8NBC634, and Yb8NBC102 Alu insertions, for MID193, MID1705, MID3754, MID3756 and MID1540 Indels and for rs6639398, rs5986751, rs5964206, rs9781645, rs2209420, rs1299087, rs318173, rs933315, rs1991961, rs4825889, rs1781116, rs1937193, rs1781104, rs149910 and rs652 SNPs. No deviations from Hardy-Weinberg equilibrium were observed for Posadas and Corrientes. However, Eldorado showed significant values, and it was found to have an internal substructuring with two groups of different origin, one showing higher similarity with European countries, and the other with more similiarities to Posadas and Corrientes. Fst pairwise genetic distances emerged for some markers among the studied populations and also between our data and those from other countries and continents. Of particular interest, Alu insertions demonstrated the most differences, and could be of use in ancestry studies for these populations, while INDELs and SNPs variation were informative for differentiation within the country.